Does Gender Matter in the Relationship between Anxiety and Decision-Making? - Zhang, Fenghua; Xiao, Leifeng; Gu, Ruolei (Frontiers in Psychology, 2017)
There is an ongoing debate about whether and how anxiety level affects behavioral performance in risk and/or ambiguous decision-making. According to the literature, we suggest that gender difference might be a confounding factor that has contributed to heterogeneous findings in previous studies. To examine this idea, 135 students who participated in this study were divided into six groups according to their gender (male/female) and trait anxiety level (high/medium/low; measured by the Trait form of Spielberger’s State-Trait Anxiety Inventory). All groups finished the Iowa Gambling Task (IGT) for ambiguous decision-making, and the Game of Dice Task (GDT) for risk decision-making. Behavioral results revealed that the IGT but not the GDT showed an interaction between anxiety and gender. Specifically, men outperformed women in the IGT, but only when their trait anxiety levels were low. Meanwhile, the GDT showed a main effect of anxiety grouping, such that low anxious participants were more risk-seeking than their medium anxious counterparts. These findings indicate that gender selectively modulates the influence of anxiety on ambiguous decision-making, but not risk decision-making. The theoretical and practical implications of the current findings are discussed.